PENILAIAN LIVABILITY RUMAH KHUSUS KOTA MAGELANG - Fadia Pratista Adiratna Dewi; Swasto, Deva Fosterharoldas (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
Home is a physiological/basic need for humans that must be fulfilled, and there is a relationship between the economic and social needs of residents through stimulus, identity, and security so that it becomes a part of development in urban areas. The comprehensive and systematic particular house building infrastructure that the Magelang City Government has built has so far been assessed through Post Occupancy Evaluation but has not been evaluated in terms of the impact on the quality of life of the residents as well as the social and economic impact so that unique houses are seen as not only accessible to MBR but comfortable as a place to live. Live in a home that is suitable to live in, relaxed, and safe (livable). The Wates Special House and the Kedungsari Special House were initially intended for carrying laborers and hawkers. Still, they were shifted to MBR people in Magelang City who were already married but did not yet own a house. The research objective is to assess the livability condition of the Wates Special House and the Kedungsari Special House. The deductive method with mixed analysis is used in research where qualitative data is the primary analytical tool, supported by quantitative data and descriptive study. Qualitative data was collected using a purposive sampling technique with 48 respondents who were residents of the Wates Special House and 23 who were residents of the Kedungsari Special House as residents of the particular house. The quantitative data collection method uses convenience sampling techniques through a 1-4 Likert scale questionnaire. Fifty-five criteria influence the assessment of the livability of unique houses, which are divided into seven aspects, including the physical unit of unique houses; exceptional home safety and security; reach of public facilities around the particular house; exceptional in-house amenities; particular home social; specialty home economics; as well as the quality of services provided by the UPT for unique houses/flats in Magelang City. The assessment results, according to residents' perceptions, show that all criteria have a negative gap value with a value ranging between -0.02817 to -0.85915, meaning that the condition of the Wates Special House and Kedungsari Special House has not met the residents' expectations based on the gap value, the condition of the Wates Special House and Kedungsari Special House including into the medium category with an average gap value of -0.23